Integrating ecosystem technology into coastal and marine infrastructure: biodiversity assessments and methodologies for comparative analyses - Leit, Aliza; Rosenberg, Yaeli; Belmaker, Jonathan; Sella, Ido (Frontiers in Climate, 2025)
The integration of “greening the gray” (GTG) into marine infrastructure represents a transformative approach to enhancing biodiversity and ecosystem services in heavily modified environments. However, the ecological effectiveness of GTG remains hindered by inconsistent methodologies and knowledge gaps. This study proposes a methodological approach for GTG biodiversity assessments, focusing on appropriate control site selection, integration of count and coverage data through occupancy methods, and applying coverage-based rarefaction to address sampling biases. The approach facilitated consistent evaluation of biodiversity data and reliable evaluation of GTG performance across various contexts, specifically using a GTG project at the Port of Vigo in Spain as a case study. This methodology structure supports sustainable marine infrastructure development by providing scalable, evidence-based methodologies for biodiversity assessment and fostering international collaboration among ecologists, developers, and stakeholders.